A Mutation of a Putative NDP-Sugar Epimerase Gene in Ralstonia pseudosolanacearum Attenuates Exopolysaccharide Production and Bacterial Virulence in Tomato Plant - Hyoung Ju Lee; Sang-Moo Lee; Minseo Choi; Joo Hwan Kwon; Seon-Woo Lee (The Plant Pathology Journal, 2023)
Ralstonia solanacearum species complex (RSSC) is a soil borne plant pathogen causing bacterial wilt on various important crops, including Solanaceae plants. The bacterial pathogens within the RSSC produce exopolysaccharide (EPS), a highly complicated nitrogen-containing heteropolymeric polysaccharide, as a major virulence factor. However, the biosynthetic pathway of the EPS in the RSSC has not been fully characterized. To identify genes in EPS production beyond the EPS biosynthetic gene operon, we selected the EPS-defective mutants of R. pseudosolanacearum strain SL341 from Tn5-inserted mutant pool. Among several EPS-defective mutants, we identified a mutant, SL341P4, with a Tn5-insertion in a gene encoding a putative NDP-sugar epimerase, a putative membrane protein with sugar-modifying moiety, in a reverse orientation to EPS biosynthesis gene cluster. This protein showed similar to other NDP-sugar epimerases involved in EPS biosynthesis in many phytopathogens. Mutation of the NDP-sugar epimerase gene reduced EPS production and biofilm formation in R. pseudosolanacearum. Additionally, the SL341P4 mutant exhibited reduced disease severity and incidence of bacterial wilt in tomato plants compared to the wild-type SL341 without alteration of bacterial multiplication. These results indicate that the NDP-sugar epimerase gene is required for EPS production and bacterial virulence in R. pseudosolanacearum.